High resolution rotational spectroscopy of elusive molecules at the Center for Astrochemical Studies (CAS@MPE). Issue Volume 15:Issue S350(2019) (April 2019) - Spezzano, Silvia; Lattanzi, Valerio; Laas, Jacob; Chantzos, Johanna; Bizzocchi, Luca; Prudenzano, Domenico; Caselli, Paola
Abstract: The laboratories at the Centre for Astrochemical Studies at the Max Planck Institute for Extraterrestrial Physics are devoted to spectroscopic studies of molecules of astrophysical relevance. In particular, in this paper we report on the two experiments that can produce and probe unstable molecules, like radicals and ions.